Desk–Mobile Computer to Increase Ergonomic in Driving - A. Sofwan; B. Sudirman (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Desk-mobile computer is a modified desk-top. It was created to provide need of entertainment and wordprocessing in the car. The mass production of the similar type of desk-mobile was produce by Bentley Company.It will be powerful, cheaper, easy to replace part and upgrading. It can be compared with notebook and otheradditional car entertainment. Data stored in hard disk 2, 5 inch and Files consist of any games and wordprocessing. Micro-ATX and Mini-ITX motherboard are chosen because the minimal dimensional character. DCACinverter provides 220Volt that will be used in power supply. LCD monitor is used as a display and TV tunerwill receive TV signal. Air flow can be used for cooling a system and Capacitor bank can stabilize DC voltage.Desk mobile computer is a innovative solution to be present computer in your car. DMC can present ergonomicto your eyes because of the large LCD monitor and better resolution. Good quality 5.1 surround system can bean enjoyment in using DMC. DMC also give a less expansive solution.Keywords: Desk-Mobile Computer (DMC), DC to AC Inverter, Motherboard, Harddisk, Cassing up-grade andenjoyment.